TECHNOLOGY PROSPECTING ON ENZYMES: APPLICATION, MARKETING AND ENGINEERING - Li, Shuang; Yang, Xiaofeng; Yang, Shuai; Zhu, Muzi; Wang, Xiaoning (Computational and structural biotechnology journal, 2012)
Enzymes are protein molecules functioning as specialized catalysts for chemical reactions. They have contributed greatly to the traditional and modern chemical industry by improving existing processes. In this article, we first give a survey of representative industrial applications of enzymes, focusing on the technical applications, feed industry, food processing and cosmetic products. The recent important developments and applications of enzymes in industry are reviewed. Then large efforts are dedicated to the worldwide enzyme market from the demand and production perspectives. Special attention is laid on the Chinese enzyme market. Although enzyme applications are being developed in full swing, breakthroughs are needed to overcome their weaknesses in maintaining activities during the catalytic processes. Strategies of metagomic analysis, cell surface display technology and cell-free system might give valuable solutions in novel enzyme exploiting and enzyme engineering.